Sports Diplomacy of Norway - Kobierecki, Michał Marcin (International Studies. Interdisciplinary Political and Cultural Journal, 2017)
Norway is perceived as a country with a clear international identity. The aim of the article is to investigate the sports diplomacy of Norway and to examine its influence on the international brand of this country. The author will define the term “sports diplomacy” and attempt to outline the strategy of Norway’s public diplomacy; an analysis of the methods used in Norwegian sports diplomacy will follow. The main hypothesis of this paper is that sports diplomacy only plays a subsidiary role in Norwegian nation branding.